2009
DOI: 10.1016/j.ahj.2009.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Association of aortic valve calcification to the presence, extent, and composition of coronary artery plaque burden: From the Rule Out Myocardial Infarction using Computer Assisted Tomography (ROMICAT) trial

Abstract: Background-Aortic valve calcification (AVC) is associated with cardiovascular risk factors and coronary artery calcification. We sought to determine whether AVC is associated with the presence and extent of overall plaque burden, as well as to plaque composition (calcified, mixed, and noncalcified).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 29 publications
1
25
0
4
Order By: Relevance
“…AVC scores increased faster with higher baseline AVC score, showing that calcium begets calcium in the aortic valve as well as arteries 87 . similar results were seen in symptomatic patients, with a significant association between prevalence of AVC and prevalence of aortic calcification and CAC and extent of CAC 88,89,90,91 . A smaller study found no correlation between baseline AVC and CAC although there was a significant correlation between the extent of annual progression of CAC and AVC 92 .…”
Section: Aortic Valvesupporting
confidence: 70%
See 3 more Smart Citations
“…AVC scores increased faster with higher baseline AVC score, showing that calcium begets calcium in the aortic valve as well as arteries 87 . similar results were seen in symptomatic patients, with a significant association between prevalence of AVC and prevalence of aortic calcification and CAC and extent of CAC 88,89,90,91 . A smaller study found no correlation between baseline AVC and CAC although there was a significant correlation between the extent of annual progression of CAC and AVC 92 .…”
Section: Aortic Valvesupporting
confidence: 70%
“…A number of authors have linked the development of valvular calcification to atherosclerosis, citing the fact that both are actively regulated processes with histological, risk factor and CV outcome similarities 129,130,131,132,133,134,135,136,137,138,139 . Furthermore, takasu et al noted that all patients with progression of AVC had progression of CAC, while 80% of those with stabilisation of AVC also had stable CAC, indicating parallel development 140 .…”
Section: Valvular Calcification -Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…moving parts increase the risk of stroke and death by 17-fold). AA is often associated with atherosclerosis in other vascular beds such as the carotid artery and coronary arteries [3]; an association with severe calcific aortic stenosis and mitral annular calcification has also been observed. These conditions are predisposed to embolisms and therefore aortic atheroma may be a marker of other disease states causing stroke [4,5].…”
Section: Case Reportmentioning
confidence: 99%